The Implementation of Old Age Security Claim Accounting Information System: Case Study of BPJS Ketenagakerjaan Palu Branch - Shinta Yunita Sari; Rahayu Indriasari; Femilia Zahra; Selmita Paranoan (International Forum of Researchers and Lecturers, 2025)
This study aims to examine how the Old Age Security (Jaminan Hari Tua/JHT) claim process is carried out at the Palu Branch of BPJS Ketenagakerjaan, both through direct services at the office and online. The main focus is on how the accounting information system supports the claim process, starting from registration, data validation, approval, transaction recording, to payment. This research uses a descriptive qualitative method through interviews with several BPJS employees in the service and finance departments. The results show that the use of digital systems such as SMILE and the JMO application has made the claim process faster and more efficient, especially for online claims. However, some obstacles remain, such as data input errors and participants' lack of understanding of digital technology. Nevertheless, the integrated system helps reduce administrative burdens as data is directly connected to the central system without the need for manual processing at the branch office. These findings indicate that the implemented information system has been running effectively and efficiently, although assistance to participants is still needed to improve the success of digital claim services.